Mycobacterial Prevalence and Antibiotic Resistance Frequency Trends in Taiwan of Mycobacterial Clinical Isolates From 2002 to 2014. Issue 12 (March 2016) - Shiau, Ming-Yuh; Lee, Ming-Shih; Huang, Tian-Lin; Tsai, Jen-Ning; Chang, Yih-Hsin
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Tuberculosis, caused by Mycobacterium tuberculosis complex (MTBC) infections, is one of the most widespread infectious diseases worldwide. Nontuberculous mycobacteria (NTM) also cause chronic pulmonary infections, however, NTM infection is generally overlooked. This study analyzed the frequencies of MTBC and NTM clinical isolates from 181, 132 specimens obtained from patients in Taiwan suspected of having a pulmonary mycobacterial infection from 2002 to 2014. The resistant rates to 4 first-line antibiotics (isoniazid, ethambutol, rifampicin, and streptomycin) of 9079 clinical MTBC isolates were also examined by the modified agar proportion method. Overall, the mycobacterial isolation rate was 8.65%, and this consisted of MTBC isolation rate of 5.01% and NTM isolation rate of 3.63%. The prevalence of MTBC isolates among the identified mycobacterial strains could be seen to decrease significantly from 82.5% in 2002 to 41.18% in 2014. Notably, the corresponding NTM prevalence increased 3.36 fold from 17.54% in 2002 to 58.82% in 2014. The frequencies of MTBC and NTM isolates showed a reciprocal trend with the crossing over occurring in the years 2010 and 2011. Although the resistance rates of the MTBC isolates to isoniazid and streptomycin were relatively stable over the study period, resistance rates of the MTBC isolates against rifampicin and ethambutol fluctuated across the study period. Overall, the incidence of multidrug resistance was relatively consistent at about 1.74%. The diagnosis, identification, and susceptibility tests for NTM should be standardized and integrated into appropriate clinical settings to cope with the increase in NTM infections. In addition, the documentation of the antibiotic resistance rates of MTBC clinical isolates to the antibiotic treatments most often clinically prescribed over a decade provides valuable clues and reference points for effective mycobacterial control.